EVALUASI TITIK KONTROL TINGGI UNIVERSITAS NEGERI SEMARANG DENGAN METODE PENGUKURAN KERANGKA DASAR VERTIKAL BENCH MARK (BM) - Safrel, Ispen (Semarang State University, 2010)
Abstract: In 2009, State University of Semarang (UNNES) had engaged in the measurement of the FrameworkÂ forÂ theÂ HorizontalÂ andÂ VerticalÂ BasicÂ FrameworkÂ usingÂ GlobalÂ PositioningÂ Systems (GPS)Â geodeticÂ typeÂ andÂ installationÂ ofÂ twoÂ benchÂ markÂ (BM),Â howeverÂ theÂ heightÂ ofÂ its developmentÂ (Z)Â in aÂ region onÂ the surface ofÂ the earth always changing and growing discourse according to some, especially for the city of Semarang itself reportedly decreased Â± 5 cm from the average seaÂ level (MSL) each year. What aboutÂ the height of Campus UNNES have now?,Â InÂ this study need to be investigated how much elevation change from a position (Unnes campus) in 2010. Measurement of vertical control framework BM Unnes tied to the High Point Geodesy (TTG) with a height of 221 004 449 number MSL in the area